Implementación de un proceso de exoneración masiva en la compañía de transporte Leonaexpress S.A. - Tinoco Tinoco, Jairo David (2015)
Ecuador, which sets the value of the property tax on motor vehicles and the exoneration of the 100% to public transport vehicles owned by professional drivers. The proposal is to make a guide that shows the process of all the activities in a clear and precise form that must be followed to carry out the procedure for exoneration massively in the company of transport LeonaExpress S.A. optimizing its economic resources. The project's feasibility analyzes on the basis of the technical dimension, economic, social and environmental, obtaining as a result of this analysis that the implementation is feasible and beneficial for the company's partners and for any company or cooperative of transportation that requires apply for exemption